Bibliometric Exploration of Sustainable Development Goals (SDGs) in the Agricultural Sector - M.Rasda; Muhammad, Mukmin; Adrianah; Akil, S.Rifatullah (Meraja journal, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal